The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/laps.12002
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Consequences of Politics: A Research Agenda for the Study of Bureaucratic Politics in Latin America

Abstract: The study of the bureaucracy in Latin America, within the study of politics, has long been little more than an afterthought. It is assumed to lie in the realm of public administration, distinct from other regional subfields that have increasingly gained the attention of political scientists. As a result, scholars' understanding of Latin American bureaucratic politics is limited. Here, we conduct a comprehensive survey of peer‐reviewed articles to evaluate the state of this subfield. We find a thematically, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…As Polga-Hecimovich and Trelles (2016) highlight, there are few studies with valuable information on the development and evolution of public agencies and the role that political actors have in the agencies’ administrative reorganizations. This article has contributed to testing how theory in bureaucratic politics applies to Latin America, and specifically to understand how the Office of the President in Colombia has historically undergone transformations in its internal structure as a result of a rational decision by the president.…”
Section: Discussionmentioning
confidence: 99%
“…As Polga-Hecimovich and Trelles (2016) highlight, there are few studies with valuable information on the development and evolution of public agencies and the role that political actors have in the agencies’ administrative reorganizations. This article has contributed to testing how theory in bureaucratic politics applies to Latin America, and specifically to understand how the Office of the President in Colombia has historically undergone transformations in its internal structure as a result of a rational decision by the president.…”
Section: Discussionmentioning
confidence: 99%
“…Others argue that Weberian bureaucracies may not even be universally desirable—that alternative types of bureaucracies, such as those that collect their own revenues, may be more suitable for developing countries (Ang 2017). Until now, however, few studies have examined the mechanisms through which accountability initiatives targeted at fighting corruption affect bureaucratic capacity (Bertelli et al 2020; Meier et al 2019; Polga-Hecimovich and Trelles 2016).…”
Section: Bureaucratic Capacity and Accountabilitymentioning
confidence: 99%
“…The notion of bureaucratic capacity, while the possibility of implementing a policy without external or personalist influence, combined with the political autonomy of the institution, is used to assess governance and, with it, build a ranking of public institutions, with several examples in Latin America (Polga-Hecimovich & Trelles, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As we will try to show, there is a strong link between union and social movements by the ruling elite of the Brazilian Federal Executive where the choice of leaders occurs in a network of broader relations, not only partisan, but with a focus on loyalty, including in patronage relations, that replaces meritocracy. Polga-Hecimovich and Trelles (2016) analyzed more than 15 thousand publications on bureaucracy in Latin America, between 2000 and 2015. They concluded that there was a relative theoretical and methodological insufficiency, whose embryonic stage in the field of studies would be characterized by the great attention spent on conceptualizing and measuring state and bureaucratic capacity, autonomy and control.…”
Section: Theoretical Frameworkmentioning
confidence: 99%